Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan di PT Bretonia - Aan Gunawan; Syamsul Arifin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Customer satisfaction is a crucial factor in the service industry, including PT Bretonia Marble, which faces challenges in maintaining service quality standards amidst global competition. This study aims to measure the impact of service quality on customer satisfaction at PT Bretonia Marble. The research method used is quantitative with a correlational approach. Primary data was obtained through questionnaires distributed to a sample of the company's customers, while secondary data came from the company's sales reports. The independent variable in this study is service quality, and the dependent variable is customer satisfaction. Data processing was conducted using regression analysis to determine the relationship between these variables. The research results show that service quality has a significant influence on customer satisfaction, with an Adjusted R Square value of 0.645. This indicates that 64.5% of the variation in customer satisfaction can be explained by service quality, while the remaining portion is influenced by other factors such as price and product reputation. The T-test demonstrates that service quality positively impacts customer satisfaction with a significance value of 0.000. In conclusion, improving service quality at PT Bretonia Marble significantly contributes to customer satisfaction. Therefore, the company is advised to continuously enhance various service dimensions, such as reliability, empathy, and responsiveness, to maintain customer loyalty and improve market competitiveness. The study also recommends optimizing service processes and employee training to strengthen customer relationships and ensure business sustainability.